HEPATOTOXIC IMPACT OF ERYTHROMYCIN SUCCINATE AFTER ORALLY REPEATED EXPOSURE IN MALE ALBINO SWISS MICE (Mus musculus) - & Taher, Timimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was aimed to determine the effects of erythromycin on the liver of albino Swiss mice. The study sample included 12 male mice divided into 3 groups. Mice of groups 1 and 2 were orally administrated with a daily dose 50 and 100 mg/kg bw erythromycin, respectively, while group 3 served as control and administrated with 0.1 ml distilled water. The treatment continued for 14 days . The results indicated a significant increase (p<0.05) in AST, ALT, and ALP activities of group treated with 100 mg/kg of erythromycin, compared with group treated with erythromycin 50 mg/kg . The study also showed several histological alterations in the liver tissues of animals treated with 50 mg/kg of the drug, including necrosis, hydropic degeneration, central vein congestion, and blood edema. Treatment with 100 mg/kg caused cell infiltration, cell vacuolation, as well as loss of radial arrangement of hepatocytes forming the liver tissue. It can be concluded that sub acute exposure to erythromycin exerts damaging effects on liver cells of treated mice.